Influence of twin-twin transfusion syndrome on fetal cardiovascular structure and function: prospective case–control study of 136 monochorionic twin pregnancies. Issue 3 (1st September 2002) - Karatza, A A; Wolfenden, J L; Taylor, M J O; Wee, L; Fisk, N M; Gardiner, H M
Abstract : Objective: To test the hypothesis that identical twins show no inter-twin differences in cardiovascular structure or physiology in fetal life unless there has been twin-twin transfusion syndrome. Design: Unselected prospective case–control observational study of fetoplacental haemodynamics including echocardiography at a median of 24 (16.7 to 32.3) weeks, with postnatal confirmation of congenital heart disease or normality. Setting: Fetal medicine unit. Patients: 136 women with monochorionic diamniotic twin pregnancies, of which 47 fetal twin pairs (35%) had twin-twin transfusion syndrome. Results: There were no haemodynamic differences between the bigger fetus (twin 1) and the smaller co-twin (twin 2) in uncomplicated monochorionic diamniotic pairs. In twin-twin transfusion syndrome, recipient fetuses had increased aortic and pulmonary velocities compared with their donor co-twins (mean (SD): 0.73 (0.23) m/s and 0.63 (0.14) m/s), respectively, v 0.53 (0.16) m/s and 0.48 (0.10) m/s in donor twins; p = 0.003 (aortic) and < 0.0001 (pulmonary)), and also in comparison with twin 1 and twin 2. The overall prevalence of congenital heart disease was increased above that in singletons (3.8% v 0.56%; 6.9% in twin-twin transfusion v 2.3% in uncomplicated monochorionic diamniotic twins), with inter-twin discordance for defects. The prevalence in recipient twins was 11.9% (p = 0.014 v uncomplicated control twins). Conclusions: Fetuses with an identical genome but no circulatory imbalance have similar cardiovascular physiology but discordant phenotypic expression of congenital heart disease. The high prevalence of congenital heart disease in monochorionic diamniotic twins merits detailed fetal echocardiography.